Error analysis in the middle test of Writing Post-Basic written by the third semester of English education department Universitas PGRI Madiun year 2021/2022 - Rida Fahas (Journal of Research on English and Language Learning (J-REaLL), 2023)
Writing is one of the important English skills. The process to make good writing is difficult. There were errors in the writing process. Therefore, the researcher was interested in analyzing the kinds of errors in writing. The problem of this study is to identify the errors made by the third-semester students of English education department at Universitas PGRI Madiun in the academic year 2021/2022. A descriptive qualitative method is used to analyze this research. The researcher analyzed subject-verb agreement errors, verb tense errors, verb form errors, singular/plural noun ending errors, and word form errors. The steps to finding the data are: collecting the sources of the data, understanding the content of the writing, selecting the test which contains errors, analyzing the collected data, and drawing conclusions. The result of this research, from the lowest to the highest, is as follows: singular/plural noun ending errors (3.40%), subject-verb agreement errors (12.24%), verb form errors (13.61%), verb tense errors (30.61%), and the highest error is word form errors (40.14%). The suggestion of the researcher for the next researcher, there are still many aspects that can be analyzed from other kinds of errors and analyzing other skills of English such as reading, speaking, and listening concerned in the errors aspect.